2016
DOI: 10.2147/rmhp.s104311
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide-treated net ownership and utilization and factors that influence their use in Itang, Gambella region, Ethiopia: cross-sectional study

Abstract: BackgroundMalaria remains a major public health problem in Ethiopia. Consequently, Ethiopia designed the 2011–2015, Malaria Prevention and Control Strategic Plan to fight the vector. It was discovered that most of the studies conducted on the use of insecticide-treated nets (ITNs) were not in line with the strategic plan of the country. This study aimed to assess ITN ownership and utilization, and includes barriers related to its use among the target-area population at household (HH) level.Materials and method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
27
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 17 publications
(49 reference statements)
12
27
6
Order By: Relevance
“…This finding is in line with the study finding in Northern Uganda (35%) [11]. However, the finding is lower than the study finding from Bungoma Kenya (82.5%), South Eastern Nigeria (90.5%), Kilifi Kenya (70.5%), Democratic Republic of Congo (78.4%), in Eastern Ethiopia (62.4%), in Itang Ethiopia (52.3%) [9,10,13,14,16,20,21]. The possible explanation for the discrepancy could be the government of Ethiopia has invested a lot to eradicate malaria, as a result, the magnitude of malaria infection in Ethiopia declined which make them give less attention to malaria prevention and the use of bed nets.…”
Section: Discussionsupporting
confidence: 88%
“…This finding is in line with the study finding in Northern Uganda (35%) [11]. However, the finding is lower than the study finding from Bungoma Kenya (82.5%), South Eastern Nigeria (90.5%), Kilifi Kenya (70.5%), Democratic Republic of Congo (78.4%), in Eastern Ethiopia (62.4%), in Itang Ethiopia (52.3%) [9,10,13,14,16,20,21]. The possible explanation for the discrepancy could be the government of Ethiopia has invested a lot to eradicate malaria, as a result, the magnitude of malaria infection in Ethiopia declined which make them give less attention to malaria prevention and the use of bed nets.…”
Section: Discussionsupporting
confidence: 88%
“…Another studies done in Togo and Rwanda showed 71.4 and 72.3% utilization which is four fold than this result (America Association for Advancement of Science, 1991;ORHB, 2001). Similarly another study done in Kenya showed utilization of 53% (Watiro and Awoke, 2016), which is three fold of the current study finding. This might be due to geopolitics and socioeconomic differences of the study areas.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, taking ITN as a major malaria prevention tool [33], over three fourth of our study groups had enough information about the ITN although their sources were varied. However, the ITNs possession rate was found to be 64.0%, which was exactly consistent with 2016 countrywide coverage [2] but lower than the reports in Benishangul Gumuz (90.9%) [34], Arsi zone (84.2%) [20] and Gambella region (81.7%) [35] in Ethiopia. While higher than the study conducted in other similar studies in Raya Azebo and Harari, Ethiopia [32,36].…”
Section: Prevalence Of Malariasupporting
confidence: 79%